Characterization of the Populus Rab family genes and the function of PtRabE1b in salt tolerance - Zhang, Jin (BMC Plant Biol, 2018)
BACKGROUND: Rab proteins form the largest family of the Ras superfamily of small GTP-binding proteins and regulate intracellular trafficking pathways. However, the function of the Rab proteins in woody species is still an open question. RESULTS: Here, a total of 67 PtRabs were identified in Populus trichocarpa and categorized into eight subfamilies (RabA-RabH). Based on their chromosomal distribution and duplication blocks in the Populus genome, a total of 27 PtRab paralogous pairs were identified and all of them were generated by whole-genome duplication events. Combined the expression correlation and duplication date, the PtRab paralogous pairs that still keeping highly similar expression patterns were generated around the latest large-scale duplication (~ 13 MYA). The cis-elements and co-expression network of unique expanded PtRabs suggest their potential roles in poplar development and environmental responses. Subcellular localization of PtRabs from each subfamily indicates each subfamily shows a localization pattern similar to what is revealed in Arabidopsis but RabC shows a localization different from their counterparts. Furthermore, we characterized PtRabE1b by overexpressing its constitutively active mutant PtRabE1b(Q74L) in poplar and found that PtRabE1b(Q74L) enhanced the salt tolerance. CONCLUSIONS: These findings provide new insights into the functional divergence of PtRabs and resources for genetic engineering resistant breeding in tree species. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-018-1342-1) contains supplementary material, which is available to authorized users.